GARCH and TGARCH Approach to Information Linkages - Khanna, Swati; Kumar, Ashish (Indian Journal of Finance, 2020)
In this study, we examined the flow of information and knowledge between the stock market of the United States (US) and emerging Asian stock markets for a period from January 2000 – December 2017. The sample included four emerging markets of India, Indonesia, Philippines, South Korea, and one developed market of the US. Our study identified the structural breaks for all the markets and then explored the asymmetric volatility spillover between the US and all Asian markets by using an extended TGARCH model. The findings of the study reflected that shocks and information transmission from the US stock market were significant from 2007 – 2010, which was the period of the global sub-prime financial crisis, which confirms the notion that during the financial crisis, the degree of dependence between the stock markets increased. Besides this, volatility persistence was also observed from the stock market of the US to all the sample stock markets for all structural break periods, and this persistency was highest from 2015 – 2017. Further, the extent and durability of the reactions to volatility coming from the US stock market were not uniform across all Asian stock markets. The integration of emerging markets of Asia with the developed market of the US has important implications for regulators and investors.